Porównanie jakości prognozowania skal UTC(PL) i UTC(NPL) z zastosowaniem sieci neuronowej GMDH = Comparison of quality of UTC(PL) and UTC(NPL) scales prediction by means of GMDH neural network - Sobolewski, Łukasz (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
The article presents research results on predicting the deviations for UTC(PL) and UTC(NPL) timescales for data prepared in the form of time series TS1 and TS2. Better quality of prediction has been obtained for UTC(NPL) timescale.
Keywords: komputeryzacja; przyrządy pomiarowe; informatyka; technologie informacyjne